A study on the strength and durability of natural fiber composite materials for environmentally friendly automotive structural components - Fider Lumban Batu (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
This study aims to examine the strength and durability of natural fiber–based composite materials as environmentally friendly alternatives for automotive structural components. The use of sustainable materials in the automotive industry has become increasingly important due to rising global demands for carbon emission reduction, energy efficiency, and the replacement of high-impact synthetic materials. In this research, three types of natural fibers kenaf, ramie, and bamboo were employed as reinforcement in a polymer matrix. Each composite sample was prepared through fiber mixing, molding, and surface treatment processes to enhance interfacial bonding between phases. Mechanical testing, including tensile, flexural, and impact tests, was conducted to evaluate the material strength. In addition, environmental resistance tests such as water absorption and high-temperature exposure were performed to assess the material’s stability under vehicle operating conditions. The results indicate that kenaf-reinforced composites exhibit the highest tensile and flexural strength, while ramie-based composites demonstrate superior performance in impact testing. Bamboo fiber composites show lower strength values but remain suitable for non-structural automotive applications. All three natural fiber composites present relatively high-water absorption levels; however, these can be reduced through alkaline treatment. Overall, the findings confirm the significant potential of natural fiber composites as environmentally friendly automotive materials. Their competitive performance, lightweight characteristics, and abundant raw material availability make them ideal candidates for non-structural components such as door panels, dashboards, and other interior parts. These results support the advancement of automotive technology toward the utilization of sustainable and eco-conscious materials.